Experimental investigations and quantum chemical calculations of methylene diphenyl diisocyanate (MDI)-based chemically modified bitumen and its crosslinking behaviours. (1st August 2022) - Li, Tianshuai; Guo, Zhixiang; Lu, Guoyang; Liang, Dong; Luo, Sang; Hong, Bin; Wang, Dawei; Oeser, Markus
Highlights: Experimental and quantum − chemical analyses of chemically modified bitumen with MDI-based additive were performed. Physicochemical properties of MDI modified bitumen were interpreted based on the quantum − chemical calculation results. The chemical and physical interactions of MDI with bitumen molecules were analyzed at a molecular-scale. Abstract: Chemical modification of bitumen with diphenyl methane diisocyanate (MDI)-based additive provided dual benefits in improving the engineering performance of pavement and reducing carbon emissions in construction process. However, the exact nature of such modification remains great part unknown. To achieve an effective understanding of the mechanisms of MDI modification, this study combined physicochemical characterisation and density functional theory (DFT)-based quantum chemical calculation to facilitate a multiscale interpretation of the molecular interaction and crosslinking behaviours of MDI-modified bitumen. The experimental physicochemical properties of MDI-modified bitumen were interpreted by the quantum chemical calculation, which suggests that covalent crosslinking occurred based on the active sites provided by the asphaltene and resin molecules. The MDI molecules can act as bridges to connect the isolated asphaltene associations, and the crosslinked network structure can be established based on the asphaltene phase. The condensation polymerization leads to the reconfiguration of asphaltene molecules without decomposing their initial non-covalent π–stacking. As a result, a significant reinforcing and stiffening effect of MDI on the bitumen matrix can be achieved. In addition, considerable non-covalent interactions are formed between MDI and asphaltene/resin molecules, which may reduce the effectiveness of MDI to react with the accessible active sites of asphaltene and resin. Therefore, adequate heating and sufficient blending are necessary to promote the reaction of MDI with bitumen molecules. This study can help in the design of highly effective isocyanate-based additives because the fundamental properties at the molecular and micro-levels are correlated with macro-level properties.